2011
DOI: 10.1002/gcc.20845
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IGHCδ–BACH2 fusion transcripts resulting from cryptic chromosomal rearrangements of 14q32 with 6q15 in aggressive B‐cell lymphoma/leukemia

Abstract: In B-cell malignancies, genes implicated in B-cell differentiation, germinal center formation, apoptosis, and cell cycle regulation are juxtaposed to immunoglobulin loci through chromosomal translocations. In this study, we identified the BTB and CNC homology 2 (BACH2) gene as a novel translocation partner of the immunoglobulin heavy chain (IGH) locus in a patient with IGH-MYC-positive, highly aggressive B-cell lymphoma/leukemia carrying der(14)t(8;14) and del(6)(q15). Fluorescence in situ hybridization analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…A number of potential candidate genes are located in the chromosome 6q15 region, including BACH2 (BTB and CNC homolog 2), MAP3K7 (mitogen-activated protein kinase 7), GABRR1 (gamma-aminobutyric acid receptor, rho 1), GABRR2, RRAGD (Ras-related guanosine-5V-triphosphate [GTP]-binding D), and CAP8AP2 (caspase 8-associated protein 2). In an aggressive B-cell lymphoma, a cryptic chromosomal rearrangement of 14q32 with 6q15 generated an IGHCδ-BACH2 fusion transcript, which resulted in overexpression of BACH2 in the tumor [19]. Deletions of 6q15 have been observed in prostatic adenocarcinoma and pediatric T-lymphoblastic leukemia, which affect the MAP3K7 gene and the transforming growth factor β/PI3K-AKT pathways, respectively [20].…”
Section: Discussionmentioning
confidence: 98%
“…A number of potential candidate genes are located in the chromosome 6q15 region, including BACH2 (BTB and CNC homolog 2), MAP3K7 (mitogen-activated protein kinase 7), GABRR1 (gamma-aminobutyric acid receptor, rho 1), GABRR2, RRAGD (Ras-related guanosine-5V-triphosphate [GTP]-binding D), and CAP8AP2 (caspase 8-associated protein 2). In an aggressive B-cell lymphoma, a cryptic chromosomal rearrangement of 14q32 with 6q15 generated an IGHCδ-BACH2 fusion transcript, which resulted in overexpression of BACH2 in the tumor [19]. Deletions of 6q15 have been observed in prostatic adenocarcinoma and pediatric T-lymphoblastic leukemia, which affect the MAP3K7 gene and the transforming growth factor β/PI3K-AKT pathways, respectively [20].…”
Section: Discussionmentioning
confidence: 98%
“…Both BACH2 and MKL2 are involved in the growth and development of cells, and BACH2 is known to play a key role in T-cell development ( 18 ). Both genes (and the MKL2 -related gene MKL1 , in which there were 4 independent integration sites, some of which were associated with clonally expanded cells in patient 1, Table S4) have been implicated in human cancers ( 1921 ), where they were activated by DNA rearrangements that created gene fusions. The pattern of multiple integrations in MKL2 and BACH2 found in the patients cannot be the result of preferential integration because HIV integration is neither intron specific nor orientation specific ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that in all five patients there was evidence of clonal expansion of HIV-1-infected cells. One patient in particular (patient 1) presented another very interesting result: two genes, for the transcription factors MKL2 and BACH2, which are associated with cell growth and have been linked to human cancers (18,19), showed a disproportionately large number of integration sites. This was surprising because, given the general randomness of integration site selection, one would not expect to find any marked imbalance in the genomic distribution of proviruses in populations of infected cells.…”
mentioning
confidence: 99%